1992
DOI: 10.1021/j100193a067
|View full text |Cite
|
Sign up to set email alerts
|

Preferential solvation of 6-propionyl(N,N-dimethylamino)naphthalene in binary, polar solvent mixtures

Abstract: Using fluorescence spectroscopy, we have determined the extent of preferential solvation of the dye PRODAN (6propionyl(VV,7V-dimethylamino)naphthalene) in binary mixtures where one component is capable of hydrogen bonding. In mixtures of methanol with acetone, acetonitrile, or pyridine the spectroscopically determined mole fraction of the PRO• DAN-methanol complex was much higher than the methanol mole fraction. The amount of preferential solvation follows the trend acetonitrile > acetone > pyridine with corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 3 publications
0
34
0
Order By: Relevance
“…Scarlata and Zurawsky have documented this behavior with PRODAN in binary mixtures of methanol with acetone, acetonitrile and pyridine and with isooctane/acetone. 26 They found that methanol preferentially interacts with PRODAN via H-bonding, but that dielectric enrichment is not important in isooctane/acetone. In contrast to these studies both water and isopropanol can form H-bonds, but water is a stronger H-bond donor than isopropanol.…”
Section: Resultsmentioning
confidence: 99%
“…Scarlata and Zurawsky have documented this behavior with PRODAN in binary mixtures of methanol with acetone, acetonitrile and pyridine and with isooctane/acetone. 26 They found that methanol preferentially interacts with PRODAN via H-bonding, but that dielectric enrichment is not important in isooctane/acetone. In contrast to these studies both water and isopropanol can form H-bonds, but water is a stronger H-bond donor than isopropanol.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescent probes such as prodan (6-propionyl-2-dimethylaminonaphthalene) and laurdan (6-dodecanoyl-2-dimethylaminonaphthalene) are widely used in biological and biophysical research [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The fluorescence properties of prodan and laurdan have been described in the literature as simultaneously existing local-excited (LE) and twisted internal charge-transfer (TICT) states.…”
Section: 37mentioning
confidence: 99%
“…[13][14][15][16] This model provides a theoretically sound method for interpreting spectrochemical shifts in solvent mixtures and offers a methodology for separating dielectric enrichment, dielectric nonideality and specific interaction (i.e., hydrogen bonding) effects from one another. 11,15,[17][18][19][20][21][22][23][24] When a dipole is immersed in a binary solvent system with a polar and a nonpolar component, the solvent composition of its solvation sphere (the local composition) differs from the average solvent composition, even in the absence of specific solvent-solute interactions. The local composition is enriched in the polar solvent component because solvent dipole-solute dipole interactions are strongest between the solute and the polar component.…”
Section: Introductionmentioning
confidence: 99%